Adaptation disorders found among students of higher educational institutions of specialties of marine and river transport in the conditions of long-term sailing - R.P, Shevchenko (International Journal of Engineering and Technology, 2019)
In article the analysis is carried out of features of disorders of adaptation capabilities found among students of higher educational institutions of specialties of marine and river transport. On the basis of the conducted research comparative characteristic of features of violations of adaptation at junior students and senior students who have undergone floating practice in a long voyage (over 3 months) is given. An approach in development of psychocorrectional actions in groups of a research taking into account clinical and a pathopsychological features is offered.Â Â